Lactational exposure to environmentally relevant benzo(a)pyrene causes astrocytic activation and anxiety-like behavior in male mice. (April 2019) - Yang, Chuanli; Han, Peiyu; Ruan, Fengkai; Zhou, Tengjian; Luo, Bing; Qiu, Yang; Lin, Yuchun; Lin, Zhongning; He, Chengyong
Abstract: Previous studies have shown the adversely neurodevelopmental effects of exposure to benzo( a )pyrene (BaP) at early life stage. However, it is unclear the effects of lactational exposure to environmentally relevant BaP on anxiety-like behavior and the molecular mechanisms related. In this study, lactational exposure to 1 and 10 μg/kg bw BaP from postnatal day 3–21 caused anxiety-like behavior and alterations of the expressions of the neurodevelopment and anxiety-related genes in adolescence male mice using O cycle maze. Moreover, BaP exposure increased the expression level of glial fibrillary acidic protein, a typical marker of astrocytes, in hippocampus of male offspring. The release of pro-inflammatory cytokines interleukin 6 and tumor necrosis factor α was also elevated in BaP-treated offspring. Further, lactational exposure to BaP decreased the level of glutathione and the expressions of antioxidant genes ( Thioredoxin 1 and Glutaredoxin 2 ) in male offspring. Our study demonstrated that environmentally relevant BaP lactational exposure caused anxiety-like behavior in male offspring involved in astrocytic activation, neuroinflammation, and antioxidant capability dysfunction. Graphical abstract: Image 1 Highlights: Lactational exposure to BaP causes anxiety-like behavior in male offspring. BaP exposure also activates astrocytes and induces the release of IL-6 and TNF-α. BaP exposure decreases of glutathione and the expressions of antioxidant genes.